Assessing combining ability of doubled haploid maize (Zea mays L.) breeding lines for grain yield and yield components under heat stress condition - Patil, S. Vinutha; Doggalli, Gangadhara; Kuchanur, Prakash H.; Zaidi, Pervez Haider; Patil, Ayyanagouda; Arunkumar, B.; Vinayana, M.T.; Tembhurne, B.V.; Suma, T.C.; Seetharam, K. (Sciencedomain International, 2022)
Maize (Zea mays L.), a leading cereal worldwide and staple food of many countries, is a multipurpose crop used for human food, animal feed and industry purposes. Maize has wider genetic adaptability to grow under different agro-ecological environments. 29 and 48 DH lines derived from MPS 1 and MPS 2, respectively, were crossed with more than one testers belonging to opposite heterotic in L x T fashion. The resultant double haploid testcrosses, and their parents were evaluated along with checks during kharif (in South Asia: the autumn crop sown at the beginning of the summer rains) 2019 at three locations. Among female lines of MPS1, DH line ZL19337 was identified as good general combiner and registered significant negative GCA effect for days to 50 per cent anthesis and days to 50 per cent silking. While, DH lines ZL19641 and ZL19357 recorded significantly positive GCA for plant height and grain yield, respectively. Among female lines of MPS 2, DH line ZL19492 was identified as good general combiner and recorded significant negative GCA effects for days to 50 per cent anthesis, and days to 50 per cent silking. Similarly, DH lines, ZL19534 and ZL19572 were identified as good general combiners for grain yield and ear position, respectively. Among testers of MPS1, ZL1840 was identified as the good general combiner for days to 50 per cent anthesis, days to 50 per cent silking and plant height and CAL14113 for ear height and grain yield. Similarly, VL1010996 was identified as the good general combiner for days to 50 per cent anthesis, days to 50 per cent silking, plant height, ear height, ear position and grain yield in MPS 2. Hybrid ZH2063 exhibited desired SCA effects for days to 50 per cent anthesis and days to 50 silking and ZH2010 was identified as a good specific combiner for days to 50 per cent anthesis and grain yield in MPS 1. Hybrid ZH20158 recorded desirable SCA effects for the trait days to 50 silking, While, ZH20251 and ZH20183 were identified as good specific combiners for plant height and grain yield in MPS 2.